2015
DOI: 10.1111/bjet.12258
|View full text |Cite
|
Sign up to set email alerts
|

Does pressing a button make it easier to pass an exam? Evaluating the effectiveness of interactive technologies in higher education

Abstract: The aim of this paper was to evaluate how audience response system (ARS) technology may increase improvements in academic performance in higher education, using the first year of the Administration and Business Management degree course at the University of Seville (Spain) as a case study. The experiment assesses whether the use of ARSs increases the likelihood that students will pass the final examinations in the subject of Principles of Economics. An econometric model is applied to a sample of 119 students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… Bordoloi (2016) offered a solution to derive the optimal mixture of classroom and online platforms by developing a mathematical model. Castillo-Manzano et al. (2016a) assessed whether the use of audience response system ICT increases the likelihood of students passing the final examinations and found that using the ICT frequently than just as a sporadic event during the course enhances the outcome.…”
Section: Introductionmentioning
confidence: 99%
“… Bordoloi (2016) offered a solution to derive the optimal mixture of classroom and online platforms by developing a mathematical model. Castillo-Manzano et al. (2016a) assessed whether the use of audience response system ICT increases the likelihood of students passing the final examinations and found that using the ICT frequently than just as a sporadic event during the course enhances the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…From an academic point-of-view, as Blasco-Arcas, Buil, Hern andez-Ortega, and Sese (2013) and Rothman (2014) state, research on the use of ARS applications in teaching is quite recent, although studies can be found that cover different academic levels and a range of disciplines. By education level, most studies focus on the university environment, where experiments have been carried out in a number of disciplines in the Experimental Sciences (Addison, Wright, & Milner, 2009;Nicol & Boyle, 2003), the Health Sciences (Levesque, 2011;Patterson, Kilpatrick, & Woebkenberg, 2010) and the Social Sciences (Castillo-Manzano, Castro-Nuño, Sanz Díaz, & Yñiguez, 2015;Stowell & Nelson, 2007). Studies have also been carried out at pre-university levels (Wash, 2012) for both primary education (DeSorbo et al, 2013) and secondary education (Barnes, 2008;Kay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the importance of teachers’ ability to design learning tasks and materials, and appropriately apply technologies in education is internationally recognized [ 48 , 125 ]. Innovative teaching approaches, new learning strategies, and the use of innovative technologies are necessary to develop students’ generic and specific competencies [ 11 ]. In this semester-long experiment, the TR strategy helped students significantly develop their programming skills and increased the level of refusal self-efficacy of Internet use; thus, the authors of this study propose that the TR strategy could enhance students’ learning performance.…”
Section: Conclusion and Directions For Future Workmentioning
confidence: 99%